Upaya Meningkatkan Hasil Belajar Pada Materi Keragaman Bentuk Muka Bumi Melalui Metode Inkuiri pada Siswa Kelas VII.B SMP Negeri 3 Gunungputri Kabupaten Bogor Tahun Pelajar 2012/2013 - Yulia Suhartati (Institut Agama Islam Sahid (INAIS) Bogor, 2020)
The author's research was carried out because it was motivated by low social studies learning outcomes and the lack of student activity on the Diversity of Earth's Shapes material made teaching and learning activities passive and tended not to attract students' attention. If this is left unchecked without any real effort from the teacher, then there is a possibility that the teacher will experience the same problem as the previous semester. Taking into account these conditions, I as a social studies teacher feel interested and want to fix this problem by improving the quality of the teaching and learning process, especially on the Diversity of Earth's Shapes by applying the inquiry learning method. The research was conducted at SMPN 3 Gunungputri from September to November 2012. The research subjects were class VII.B, which consisted of 43 students. The method used is classroom action research, which consists of two cycles. Each cycle consists of four stages, namely: 1) planning; 2) implementation; 3) observation; and 4) reflection. The results of the study conclude that: 1) Learning with the inquiry method can increase the activity of students and teachers, in the learning process in the first cycle by 81% and in the second cycle by 87%, 2) Learning with the inquiry method can improve student learning outcomes, and 3) The percentage of student learning outcomes in the first cycle is 72.09% and in the second cycle is 81.40%. By using the Inquiry method on the Diversity of Earth's Forms Material, student learning outcomes can be increased.